THE EFFECT OF SELF DIRECTED LEARNING READINESS (SDLR) AND LEARNING APPROACH TOWARD MEDICAL STUDENT ACHIEVEMENT - Nurul Amaliah Lestari; Uswatun Hasanah; Ricardi Witjaksono Alibasjah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Learning approach and Self Directed Learning Readiness (SDLR) are important factors that influence student learning achievement. The world of medical education has experienced a paradigm shift from Teacher-Centered Learning (TCL) to Student-Centered Learning (SCL) that is applied through the Problem Based Learning (PBL) methods that expected the student to have the ability to learn independently or what is called Self Directed Learning (SDL). This study aimed to analyzed the effect of SDLR and learning approach on medical student achievement.Methods : this study uses a cross-sectional design. The sample was students of the Faculty of Medicine, Swadaya Gunung Jati University, 2016, 2017 and 2018 as many as 181 people. The sampling technique uses stratified random sampling. Spearman test, chi-square test and linear regression test were used to analysed the effect of the age, SLDR and learning approach on medical student achievementResults : The chi square test result in this study showed that age (P = 0.001; rs = 0.359), SDLR (P = 0.001; rs = 0.516) and the learning approach (P = 0.001; rs = 0.308) had a significant effect on medical students' learning achievement. However, there was no significant difference in the learning approach between 2016, 2017 and 2018 classes. The linear regression test results showed that SDLR was the most influential variable in the learning achievements of medical students.Conclusions : Self Directed Learning Readiness (SDLR) and learning approach could be the effective learning methods. SDLR as the most effective method to increase the learning achievements of medical student could be applied on many medical schools.